Analisa Manajemen Proyek Pada Pemanfaatan Limbah Stik Es Krim Menjadi Lampu Tidur - Davis Reandy; Ferdawson Ferdawson; Rich Jackson; Yuli Indah Fajar Dini (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2024)
This waste used from ice cream sticks will be transformed into a lantern with contemporary aesthetics that can function both as equipment and ornament. The issue of needs and desires, or fulfilling needs, always confronts humanity. Needs are requirements for human survival; among them are economic needs, which are basic needs for society and are therefore met through various work patterns, procedures and strategies. Continuous efforts to meet needs require rational behavior from individuals, which requires action to prevent inefficiency and waste. Conclusion Specific criteria, such as the amount of active components, safety standards, and microbiological test results, are necessary to evaluate tissue quality. It is important to carry out thorough testing at every stage of the production process to guarantee that recyclable containers are of the highest quality.